2012
DOI: 10.1016/j.neuint.2012.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of neuronal bioenergy homeostasis by glutamate

Abstract: Bioenergy homeostasis is crucial in maintaining normal cell function and survival and it is thus important to understand cellular mechanisms underlying its regulation. Neurons use a large amount of ATP to maintain membrane potential and synaptic communication, making the brain the most energy consuming organ in the body. Glutamate mediates a large majority of synaptic transmission which is responsible for the expression of neural plasticity and higher brain functions. Most of the energy cost is attributable to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 66 publications
2
23
0
Order By: Relevance
“…Our results are consistent with the previous report that spine damage is a preceding neuropathological process contributing to neuronal injury after stroke, possibly due to the high sensitivity of synaptic activity to alterations in energy supply ( Khatri and Man 2013 ). For example, results from magnetic resonance spectroscopy related the changes in neuroenergetics revealed that more energy were required for functional activation to neurotransmitter cycling at the level of the synapse ( Waldvogel et al 2000 ; Foo et al 2012 ). And the structural and functional integrity of synaptic transmission profoundly depends on a superior oxygen and glucose supply ( Acker and Acker 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with the previous report that spine damage is a preceding neuropathological process contributing to neuronal injury after stroke, possibly due to the high sensitivity of synaptic activity to alterations in energy supply ( Khatri and Man 2013 ). For example, results from magnetic resonance spectroscopy related the changes in neuroenergetics revealed that more energy were required for functional activation to neurotransmitter cycling at the level of the synapse ( Waldvogel et al 2000 ; Foo et al 2012 ). And the structural and functional integrity of synaptic transmission profoundly depends on a superior oxygen and glucose supply ( Acker and Acker 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, exposure of neurons to glutamate results in a reduction in cellular ATP levels (20) and glucose uptake in neurons (42), indicating distinct signaling and cellular responses to synaptic vs. non-synaptic glutamate receptor activation.…”
Section: Coupling Of Synaptic Activity and Energy Homeostasismentioning
confidence: 99%
“…Additional physical exercise increases the neural plasticity and the activity of neural tracts. It was well confirmed that glutamate is a main excitatory neurotransmitter, which intermediates a substantial most of synaptic transmission and neural plasticity, as well as higher brain functions [20]. Various current investigations demonstrate that physical training likewise features an critical importance in angiogenesis and practical restoration following cerebral stroke [21].…”
Section: B F Kania Et Almentioning
confidence: 88%